Spectropolarimetry of the Type Ib Supernova iPTF 13bvn: revealing the complex explosion geometry of a stripped-envelope core-collapse supernova. Issue 1 (20th January 2016) - Reilly, Emma; Maund, Justyn R.; Baade, Dietrich; Wheeler, J. Craig; Silverman, Jeffrey M.; Clocchiatti, Alejandro; Patat, Ferdinando; Höflich, Peter; Spyromilio, Jason; Wang, Lifan; Zelaya, Paula
Abstract: We present six epochs of spectropolarimetric observations and one epoch of spectroscopy of the Type Ib SN iPTF 13bvn. The epochs of these observations correspond to −10 to +61 d with respect to the r -band light-curve maximum. The continuum is intrinsically polarized to the 0.2–0.4 per cent level throughout the observations, implying asphericities of ∼10 per cent in the shape of the photosphere. We observe significant line polarization associated with the spectral features of Ca ii  ir3, He i /Na i  d, He i  λλ6678, 7065, Fe ii  λ4924 and O i  λ7774. We propose that an absorption feature at ∼6200 Å, usually identified as Si ii  λ6355, is most likely to be high-velocity H α at −16 400 km s −1 . Two distinctly polarized components, separated in velocity, are detected for both He i /Na i  d  and Ca ii  ir3  , indicating the presence of two discrete line-forming regions in the ejecta in both radial velocity space and in the plane of the sky. We use the polarization of He i  λ5876 as a tracer of sources of non-thermal excitation in the ejecta; finding that the bulk of the radioactive nickel was constrained to lie interior to ∼50–65 per cent of the ejecta radius. The observed polarization is also discussed in the context of the possible progenitor system of iPTF 13bvn, with our observations favouring the explosion of a star with an extended, distorted envelope rather than a compact Wolf–Rayet star.